THE IMPLEMENTATION OF VIDEOS TO IMPROVE THE EIGHTH YEAR STUDENTS’ SKILL IN WRITING RECOUNT TEXTS AT SMP N 1 PLERET - Vivi Fajar Wati; Nanang Bagus Subekti (Universitas Sarjanawiyata Tamansiswa, 2019)
The aims of this research are to describe (1) students’ writing skill before using video, (2) the implementation of using video technique to improve students’ writing recount text, (3) the improvement of the students’ writing skill after using video, and (4) the significant of differences between the students’ writing before and after using video. This study is action research. The researcher collected the data by doing observation during the implementation, interviews with the teacher and the students, and test for the students and documents. The finding of this research consisted of two cycles. First and second cycle provided five stages, they are observing, questioning, experimenting, associating, and communicating. In observing stage, the researcher showed the example of recount text to the students. In questioning stage, the researcher asked the students to give their opinion about the text. In experimenting stage, the researcher explained material about recount text to the students. In associating stage, the researcher provided the activities and asked the students to make recount text as a test 1. In communicating stage, the researcher asked the students to communicate their work. And second cycle, in observing stage, the researcher showed video about recount text. In questioning stage, the researcher asked the students to give their opinion about the video. In experimenting stage, the researcher explained about the generic structure and language feature of the video. In the associating stage, the researcher provided the activities and asked the students to make recount text as a test 2. In communicating stage, the researcher asked the students to communicate their work. The results of this study in teaching writing recount text using video were that firstly, teaching writing recount text improved the students’ writing in three aspects: content, organization, and language features. Secondly, the students became motivated in teaching and learning process using video.